Analisis Pengaruh Sistem Kompensasi dan Disiplin Kerja terhadap Motivasi Kerja Kurir PT. Borwita Citra Prima Surabaya - Muhammad Arif Setiawan; Akhmad Fauzi; Ika Korika Swastika (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The COVID-19 pandemic has a major impact on all business sectors, this can be evidenced by the soaring number of layoffs and cuts in labor wages in various companies. Ida Fauziyah (2021) stated that Indonesia's unemployment rate during the Covid-19 pandemic increased 4.9% to 7% or 9.7 million people. Therefore, business actors need to make effective and efficient business policies, including the Human Resource Department, which has the task of making employment policies within the company effectively and efficiently. The compensation system, work discipline, and work motivation are some of the urgent tasks of HRD during this COVID-19 pandemic. At PT. Borwita Citra Prima there are phenomena that indicate that the courier at the company is suspected of lacking good work motivation, from some of the data collected it is suspected that the source of the problem is the compensation system and work discipline of the courier in the company. On this basis, the researcher aims to obtain information about the effect of the compensation system and work discipline on the work motivation of couriers at PT. Borwita Citra Prima Surabaya. This study uses primary data obtained from respondents' answers (all couriers) in the company. To meet the research objectives, the researchers distributed a total of 60 questionnaires. Regarding the analysis, the researcher used the partial least square method with the help of PLS ​​software. From this research, two conclusions are obtained, the first is that the compensation system affects work motivation significantly (positively) with path coefficients of 0.270074, and the T-statistic value of 3.104459. The second is that work discipline affects work motivation significantly (positively) with path coefficients of 0.565998, and a T-statistic value of 7.515237.